2019
DOI: 10.1088/1757-899x/598/1/012036
|View full text |Cite
|
Sign up to set email alerts
|

The Literature Review of Cloud-based Enterprise Resource Planning

Abstract: Enterprise Resource Planning also called ERP is a system that is integrated into business processes in a company, some of the benefits of implementing ERP are higher productivity, better insights, accelerated reporting, lower risk, simpler IT and improved agility. However, ERP also has several disadvantages such as high costs, maintenance costs and this became a common problem when using the ERP system. One way to cut high costs is to use cloud computing. Cloud computing is pools of configurable computer syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Finally, from the study of Cardenas [35], it is possible to obtain data on the performance of the LTE network in smart meters through simulations, citing that his research would be helpful for future work with cloud computing, where it is corroborated in our research that it is possible, since we could take the data obtained from a similar simulation to visualisation with the help of the proposed cloud tool. It also talks about the security of cloud computing, where it could be confirmed that it is efficient, since the visualisation elements are private and to access them, an AWS account is needed with the respective permission granted by the creator of the visual element, who grants the necessary permissions to specific users to work with the information [36].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, from the study of Cardenas [35], it is possible to obtain data on the performance of the LTE network in smart meters through simulations, citing that his research would be helpful for future work with cloud computing, where it is corroborated in our research that it is possible, since we could take the data obtained from a similar simulation to visualisation with the help of the proposed cloud tool. It also talks about the security of cloud computing, where it could be confirmed that it is efficient, since the visualisation elements are private and to access them, an AWS account is needed with the respective permission granted by the creator of the visual element, who grants the necessary permissions to specific users to work with the information [36].…”
Section: Discussionmentioning
confidence: 99%
“…Abd Elmonem et al (2016) conducted an SLR of 31 articles published from 2011 to 2016, identifying the benefits and challenges of Cloud ERP implementation. Aulia et al (2019) reviewed 31 articles published from 2011 to 2016, determining the benefits and challenges before Cloud ERP implementation. Mahmood et al (2020) reviewed 53 articles published between 1999 and 2018, identifying 10 challenges faced by ERP implementation projects.…”
Section: Introductionmentioning
confidence: 99%
“…(2016) conducted an SLR of 31 articles published from 2011 to 2016, identifying the benefits and challenges of Cloud ERP implementation. Aulia et al. (2019) reviewed 31 articles published from 2011 to 2016, determining the benefits and challenges before Cloud ERP implementation.…”
Section: Introductionmentioning
confidence: 99%
“…Many previous research papers highlighting the ERP usability issues focus on the area of information systems [13][14][15]. These contributions are primarily related to the adaptation of ERP systems by the users of corporates.…”
Section: Introductionmentioning
confidence: 99%